2020
DOI: 10.1016/j.jdin.2020.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the compliance of systematic review articles published in leading dermatology journals with the PRISMA statement guidelines: A systematic review

Abstract: Background: Reporting quality of systematic reviews and meta-analyses is of critical importance in dermatology because of their key role in informing health care decisions. Objective: To assess the compliance of systematic reviews and meta-analyses in leading dermatology journals with the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement guidelines. Methods: This review was carried out in accordance with PRISMA guidelines. Included studies were reviews published across 6 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 180 publications
(25 reference statements)
1
4
0
Order By: Relevance
“…Interestingly, 36.1% of SRs included between 2010 and 2019 referred to the PRISMA statement, while a closer look at the SRs included between 2000 and 2009 reveals that hardly any of them referred to the QUOROM statement. This is supported by previous research indicating that journals have more frequently included the PRISMA guideline in their instructions to authors [ 29 , 30 ] and that author compliance has increased [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 77%
“…Interestingly, 36.1% of SRs included between 2010 and 2019 referred to the PRISMA statement, while a closer look at the SRs included between 2000 and 2009 reveals that hardly any of them referred to the QUOROM statement. This is supported by previous research indicating that journals have more frequently included the PRISMA guideline in their instructions to authors [ 29 , 30 ] and that author compliance has increased [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 77%
“…It aims to build an association model of the findings during the Systematic Literature Review. In the article that Gundogan et al (2020) evaluates the compliance of journals that used the PRISMA, a gap is signaled in this study not only being used by the health segments but also by other areas of study, also in the article it is demonstrated that general compliance with the PRISMA statement has improved the quality of publications. The PRISMA contains comprises the well-define stages of a systematic review such as developing eligibility criteria and describing information sources, search strategies, study selection processes, outcomes and data synthesis (Moher et al, 2015).…”
Section: Methodsmentioning
confidence: 73%
“…This technique ensures strong and reproducible results (Debray 2017). PRISMA has been used to improve quality of systemic review protocols and has been applied in significant number of studies related to health (Gundogan et al, 2020), disaster (Nandgude et al, 2023), education (Ardoin & Bowers, 2020), climate change (Bherwani et al, 2020a), risk management (N. Kumar et al, 2021), and engineering (Gharbia et al, 2020) among others. This SLR involves research question identification as its first step.…”
Section: Methodsmentioning
confidence: 99%